ROCK-WATER MODEL AS A BASE FOR PREDICTING THE CHEMICAL COMPOSITION OF NATURAL CRUSTAL WATERS - Ryzhenko B.N.; Krainov S.R. (My University, 2003)
The computer-assisted physicochemical modeling of hydrogeochemical processes that occur in systems of sedimentary and crystalline rocks with water has been done for the following variables: the weight ratio of the reacted rock to water (R/W), the thermodynamic openness or closeness of the rock-water system to the Earth's atmosphere, the CO 2 partial pressure, and the degree of extraction of volatiles from the rock in the temperature range 25-200°C and the pressure range 0.001-3 kbar. A comparison of the modeling results and natural observations has shown that the rock-water-gas model developed reconstructs settings in which the chemistry of all major types of natural waters was formed. This model can be used in predicting the chemical evolution of water in response to changes in the water-exchange time and to natural and human impacts.